Substitutional Vanadium Sulfide Nanodispersed in MoS2 Film for Pt‐Scalable Catalyst (Adv. Sci. 16/2021). Issue 16 (18th August 2021) - Agyapong‐Fordjour, Frederick Osei‐Tutu; Yun, Seok Joon; Kim, Hyung‐Jin; Choi, Wooseon; Kirubasankar, Balakrishnan; Choi, Soo Ho; Adofo, Laud Anim; Boandoh, Stephen; Kim, Yong In; Kim, Soo Min; Kim, Young‐Min; Lee, Young Hee; et al.
Abstract : Transition Metal Dichalcogenides In article number 2003709, Young Hee Lee, Young‐Kyu Han, Ki Kang Kim, and co‐workers demonstrate the unique basal plane activation of 2D MoS2 via substituted V atom near chalcogen vacancy (VS n unit) in the lattice. The VS n units act as active sites and charge transfer pathways for efficient hydrogen evolution. This study adds insight into ways to engineer active sites in transition metal dichalcogenides electrocatalyst at the atomic level.